(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Effective communication is essential for quality healthcare delivery. However, communication skills training is often overlooked in medical education, leading to inadequate skills among young doctors and compromised patient care. This study aimed to assess the communication skills of first-year medical students and analyse their attitudes towards the importance of communication skills. Materials and Methods: A cross-sectional study was conducted among first-year medical students enrolled at Jubilee Mission Medical College in Central Kerala, India. The study employed a multi-step methodology, including a self-assessment questionnaire to evaluate participants’ communication skills, an Attitude, Ethics & Communication (AETCOM) session in the form of role plays, games, and narratives, to provide communication skill training, and a Communication Skills Attitude Scale (CSAS) questionnaire to assess students’ attitudes towards communication skills. Statistical analysis was conducted to identify patterns and correlations among the variables. Results: Out of the 99 participants, 74% self-assessed their communication skills as good. In spite of the majority of students having good communication skills, the CSAS scores, post AETCOM session, indicated more positive attitudes towards communication skills. Gender differences were observed, with male students reporting increased negative attitudes compared to female students. Conclusion: While the study revealed positive attitudes and self-assessment scores, there is still room for improvement in communication skills among medical students. Continuous training throughout medical education, along with targeted interventions addressing gender differences should be implemented to create an inclusive and supportive learning environment.